International accreditation and quality medical education (Colombia Medica, 2013)
The Pan American Federation of Associations of Faculties (Schools) of Medicine - FEPAFEM/PAFAMS - is a non-governmental, on-profit academic organization that joins the National Associations of Medical Schools for the Hemisphere. For some countries the growth in the number of schools and colleges has been explosive in recent decades to where now there are, in fact, about 706 medical schools in the Americas: 181 in North America, 190 in Central America and the Caribbean region and 335 in South America. This represents approximately 31% of the world total. Of these, 559 (79%) of the hemisphere´s medical schools are affiliated with FEPAFEM/PAFAMS.